Possible contribution of β-glucosidase and caspases in the cytotoxicity of glufosfamide in colon cancer cells - Arafa, Hossam M.M. (European journal of pharmacology, 2009)
Glycoconjugates represent a recent trend in cancer chemotherapy that adopts the concept of selective prodrug/drug targeting of tumor cells by binding to specific transmembrane glucose transporters. Following preferential uptake of sugar conjugates into cancer cells, they are presumably subject to enzymatic cleavage by specific β-glycosidases to liberate the free active cytotoxic aglycones that act selectively on cancer cells and spare other noncancerous ones. In this sense, the role of β-glucosidase and caspases in the bioactivation and cytotoxicity of glufosfamide has been addressed in the current study. The cytotoxicity of glufosfamide has been investigated over 24–96 h in a panel of human colon cancer cells namely, Caco-2, HT29 and T84 using a tetrazole dye; 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide; MTT assay technique. Apoptosis was assessed by fluorometric assay of caspase-3 and caspase-9 activities. Enzymatic cleavage of glufosfamide was accomplished using a host of hydrolytic enzymes and cleavage kinetics was determined using HPLC. Glufosfamide has proven cytotoxic efficacy in a concentration- and time-dependent manner. The sensitivity rank order of tumor cells towards the glycoconjugate was Caco-2 > HT29 > T84. This sensitivity ranking was well correlated with the enzymatic activity of β-glucosidase assessed in these cell lines. Initiation and activation of apoptosis were increased in all colon cancer cells following exposure to glufosfamide and were well correlated with the cytotoxicity rank order of the glycoconjugate. Glufosfamide was cleaved by cytosolic and lysosomal β-glucosidases but not by other hydrolytic enzymes such as cytosolic β-galactosidase, pancreatic lipase or hepatic esterase. In conclusion, the current data could possibly unravel the mechanistic role of β-glucosidase and apoptotic caspases in the bioactivation and cytotoxicity of glufosfamide within colon cancer cells.